Future trends in cystic fibrosis demography in 34 European countries - Burgel, Pierre-Régis; Bellis, Gil; Olesen, Hanne V; Viviani, Laura; Zolin, Anna; Blasi, Francesco; Elborn, J Stuart (The European respiratory journal, 2015)
Median survival has increased in people with cystic fibrosis (CF) during the past six decades, which has led to an increased number of adults with CF. The future impact of changes in CF demographics has not been evaluated. The aim of this study was to estimate the number of children and adults with CF in 34 European countries by 2025. Data were obtained from the European Cystic Fibrosis Society Patient Registry. Population forecasts were performed for countries that have extensive CF population coverage and at least 4 years of longitudinal data by modelling future entering and exiting flows in registry cohorts. For the other countries, population projections were performed based on assumptions from knowledge of current CF epidemiology. Western European countries' forecasts indicate that an increase in the overall number of CF patients by 2025, by approximately 50%, corresponds to an increase by 20% and by 75% in children and adults, respectively. In Eastern European countries the projections suggest a predominant increase in the CF child population, although the CF adult population would also increase.It was concluded that a large increase in the adult CF population is expected in the next decade. A significant increase in adult CF services throughout Europe is urgently required.